From SnappyApp to Screens in the Wild: gamifying an Attention Hyperactivity Deficit Disorder continuous performance test for public engagement and awareness - Craven, Michael P.; Young, Zoe; Simons, Lucy; Schnädelbach, Holger; Gillott, Alinda (IEEE, 2014)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental condition that is characterised by three core behaviours: inattention, hyperactivity and impulsivity. It is typically thought that around 3-5% of school aged children have ADHD, with lifetime persistence for the majority.